Economic inequality in Latin America : migration, education and structural change - Villalobos Barría, Carlos, 1980- (Göttinger Studien zur Entwicklungsökonomik ;, 2013)
Inequality in Latin America is very large and there is a great desire for greater social justice, inclusion and equal opportunities. In order to contribute to the understanding of such developments, this volume addresses the problem of economic inequality in Paraguay, Honduras and Chile. The studies show from different angles how an adverse family background has permanent negative effects on employment, wages and labour mobility, particularly in the presence of structural economic changes. In general, this book is a contribution to understand why inequality is highly persistent in Latin Americ.